The role of the share of physical and sports education in promoting some values of social citizenship - Ben djafer, ramadan (Journal of Social Sciences and Humanities, 2020)
The aim of this study is to know the role of educational physical activities in the development and promotion of some values of social citizenship (cooperation, respect, tolerance) for students of the Department of Physical Education at the Institute of Science and Techniques of Physical and Sports Activities (University of M'sila) during the course of the session in the sports stadiums located in the Institute, as well as identifying On the image embedded in the minds of students of the institute on the subject of physical and sports education and its money from different roles in the life of the university student, and how this article helps students to create an atmosphere of cooperation, respect and tolerance among them while performing group sports activities To achieve the objectives of this study, the researcher used the descriptive approach on a sample of students from the Institute of Physical Education at the Institute, amounted to(60) male and female students among the original total of 286 students, or a percentage estimated at 21%, and statistical treatment of various By percentage. The results of this study indicated a noticeable development regarding the promotion of the values of citizenship in its social dimensions (cooperation, respect, tolerance).